2007
DOI: 10.1016/j.amjcard.2006.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atorvastatin on Vitamin D Levels in Patients With Acute Ischemic Heart Disease

Abstract: Vitamin D deficiency is a risk factor for osteoporosis and other chronic diseases, including type 1 diabetes, hypertension, metabolic syndrome, and ischemic heart disease. Cholesterol and vitamin D share the 7-dehydrocolesterol metabolic pathway. This study evaluated the possible effect of atorvastatin on vitamin D levels in patients with acute ischemic heart disease. Eighty-three patients (52 men and 31 women) with an acute coronary syndrome (75 with acute myocardial infarction and 8 with unstable angina) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
105
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 9 publications
9
105
0
3
Order By: Relevance
“…However, these levels remained insufficient (data not shown). This finding supports several previous reports which suggested that statins may increase the synthesis of calcitriol by inducing enzyme 7-dechydrocholesterol 23,24 .…”
Section: Chf Patientssupporting
confidence: 82%
“…However, these levels remained insufficient (data not shown). This finding supports several previous reports which suggested that statins may increase the synthesis of calcitriol by inducing enzyme 7-dechydrocholesterol 23,24 .…”
Section: Chf Patientssupporting
confidence: 82%
“…As a result, however, we did not include iCa as a confounder in multiple linear regression analyses, because EuroSCORE was not signifi cantly correlated with iCa in simple linear regression analysis. Additionally, we included statin therapy as a covariate, because statin therapy has been shown to increase circulating vitamin D levels (20) and may be a confounder behind the negative association between 25OHD as well as 1,25OHD levels, and Euro-SCORE (21). In contrast, we did not use underlying diseases (i.e., CAD, VHD and AD) as confounders because EuroSCORE already accounts for these operation-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrate that rosuvastatin increases the blood level of vitamin D as 25-hydroxyvitamin D and also the activated hormone 1,25-dihydroxyvitamin D. This effect has also been found with atorvastatin [18]. The mechanism is unexplained and is far from clear.…”
mentioning
confidence: 90%